Pliocene trace fossils from oyster substrates in the Nijar Basin, Betic Cordillera, southern Spain. Issue 3 (June 2021) - Donovan, Stephen K.; Jones, Stuart J.; King, Abigail R.; Harper, David A.T.
Abstract: The Almería-Níjar Basin is a Neogene, intermontane depression marginal to the Mediterranean in southern Spain in the vicinity of El Argamasón, Andalucia. The Pliocene Cuevas Formation rests unconformably on the Upper Messinian rock succession in the Carboneras Fault Zone. The Cuevas Formation is a coarse-grained, bioclastic-rich, calcarenite to calcirudite shoreface deposit. Oysters, namely Saccostrea cucullata (Born), are locally common and preserve a moderate diversity of borings: Caulostrepsis taeniola Clarke; Entobia isp.; Gastrochaenolites isp. aff. G. lapidicus Kelly and Bromley; Maeandropolydora isp. cf. M. sulcans Voigt; Oichnus paraboloides Bromley; and Talpina isp. aff. T. hirsuta Voigt. All represent domiciles except for the predatory O. paraboloides trace. This suite of ichnotaxa is assigned to the Entobia ichnofacies sensu Bromley and Asgaard; they are comparable, particularly, with the Boulder Assemblage of the Pliocene of Rhodes, Greece. Physical disturbance is an important parameter in favouring this pattern of infestation, whether the bored clasts are boulders or oyster valves.